ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN ONLINE - Amru Sahmono Boang Manalu; Ujang Sumarwan; Arif Imam Suroso (Jurnal Manajemen & Agribisnis, 2007)
The objectives of this study  are to (1) analyze customer satisfaction with online shopping (2) determine factors influencing customer satisfactions with online shopping; (4) formulate strategies to increase customer satisfaction with online shopping. Data were collected from 150 respondents. The research used Structural Equation Modelling (SEM) and the software LISREL for the data processing. The result of SEM analysis reflected that all variables significantly correlated to each dimension of modified WebQual instrument and significantly influenced online customer satisfaction. There were six dimensions that were measured. They were usefulness, ease of use, entertainment, complementary relationship, customer service, and buyer-seller interaction. Satisfactions were measured through overall satisfaction and recommendation. Secured transaction was the most significant factor influencing  customer satisfaction.